The sacred king as a waste heap in northern Cameroon - (:unkn) unknown (My University, 2017)
In this article, the author considers waste (bodily excreta, the remains of daily activities, discarded artefacts) as the result of a process whereby material items are disembodied or excorporated. In the ancient kingdom of the Guiziga Bui Marva in northern Cameroon, the waste produced by each subject ended up on a large waste heap accumulated by the king. The bodily conducts of the king and his subjects were such as to identify the monarch with the heap according to the tenets of African sacred kingship. Contemporary ethnographic evidence sheds light on the history of the region and vice versa. It documents enduring bodily practices over the last couple of centuries, and the significant changes that affected them in regard to the production of given religious subjectivities.
Keywords: African Research